Image analysis of normal exfoliated gingival cells - Anuradha A; Sivapathasundharam B (Wolters Kluwer Medknow Publications, 2007)
Objective: The present study was undertaken to evaluate the nuclear diameter (ND), cell diameter (CD) and nuclear-cytoplasmic ratio (N:C) and their variation with age and sex in normal gingival smears. Study Design: Gingival smears were collected from 320 apparently healthy individuals. After fixation in 95% alcohol, the smears were stained using standard papanicolaou laboratory procedure. The cell and nuclear diameters were measured using image analysis software (KS lite 2.0). Statistical analysis of the data was done using one-way ANOVA, Students ′t′ test and Tukey-HSD procedure. Results: The results showed an increase in ND from the 1-20 group to 21-40 age group in males. Above 40 years, there was a decrease in ND. In females, the ND was high in 21-40 age group; and then from 41 years, ND gradually decreased but the difference was not significant. The CD in males and females was low in the 1-20 age group and then it gradually increased. However, the difference was not significant between the ages 20 and 60 years. After 60, there was a decrease in CD. Similar changes are also seen in the ratio N:C in both males and females. The ND, CD and N:C irrespective of the age were high in females. The difference in CD was insignificant, except in the 0-20 age group, where females had significantly more cell diameters. Irrespective of the gender, the ND, CD and N:C increased from 0-20 age group to 20-40 age group. After 40, there is a steady decrease in ND, CD and N:C. Conclusion: Age-related and sex-related alterations are observed in gingival smears.